Sexual abuse against minors in the communes of Abomey-Calavi and So-Ava in Southern Benin - Kossouoh, Ella; Houinato, Dismand; Kpatchavi, Adolphe; Sossa, Charles; Aguemon, Badirou (International Journal Of Community Medicine And Public Health, 2025)
Background: Sexual violence against children is a growing global public health issue, including in Africa. This study examines the extent and contributing factors of sexual violence among children in two communes in southern Benin (Abomey-Calavi and Sô-Ava). Methods: Using data from 125 children aged 0-18 years, identified from social promotion center records between 2018 and 2022, the study employed a non-probability and exhaustive sampling method. Eligible children, regardless of gender or nationality, were selected from Gender-Based Violence (GBV) registers. Results: The findings highlight key socio-demographic and economic factors influencing sexual violence. The average age of victims was 13.18±3.16 years, with rape being the most prevalent form of abuse. Girls constituted 91.2% of cases. Children lacking parental education were 1.2 times more likely (95% CI = [1.7836; 10.5279], p value <0.05) to experience harassment and rape. Consequences included social isolation, increased sexual activity, prolonged treatment periods, and school or professional absenteeism. Conclusions: The study underscores the need for a national action plan emphasizing parental education as a core strategy for prevention. A comprehensive communication approach targeting parents, children, social workers, and child protection systems is recommended. Additionally, strengthening law enforcement measures against sexual violence is crucial.